Evaluasi Ergonomi Lingkungan Kerja Pos Penjaga Palang Pintu Kereta Api di Gombong - Ma'arif, Imam Samsul; Hidayah, Muhammad Nur Wahyu; Munandar, Galih Mahardika; Pamungkas, Krisna Adhi; Natang, Rena Hartini (Universitas Muhammadiyah Sorong, 2025)
Railway crossing guard posts are essential outdoor workplaces that play a crucial role in transportation safety, yet they are often overlooked in ergonomic studies. Gatekeepers perform their duties with limited facilities, making them vulnerable to noise, poor lighting, high temperatures, and vibrations from passing trains. This study aims to evaluate the ergonomic conditions of the guard post in Gombong by measuring four main parameters: noise, lighting, temperature, and vibration. Measurements were conducted using standardized instruments, and the results were compared to official threshold limits. The findings revealed that the average noise level was 96 dBA, exceeding the standard of 85 dBA; nighttime lighting was 43 lux, below the minimum standard of 100 lux; daytime temperature reached 32.5 degrees Celsius, above the comfort range of 25–27 degrees Celsius; and vibration was 0.4 m/s², which remained within the safe threshold. Although exposure was short, cumulative risks could reduce concentration. This study provides practical recommendations for improving work conditions and expands research on environmental ergonomics in public transportation sectors.